The National Audiovisual Institute's African collections, between epistemological anxiety and historiographical potential - (:unkn) unknown (My University, 2023)
What has become of the audiovisual recordings captured by France in Africa during the colonization and the decolonization periods ? And to whom do they belong to ? Based on these questions and on a visit to the French National Audiovisual Institute (INA) digitized collections, this article addresses a colonial archive that remains little studied. As an archive-subject, it constitutes a stimulating place to examine colonial history. For that reason, it awaits analysis by historians of the colonization as well as by postcolonial archivists.
Keywords: African Research